Happy endings - Michael Barret (Revista Espaço Acadêmico, 2021)
Happy endings are not all alike. In fact, they're not always happy. People have many strange ideas about Hollywood movies, and it's not always clear what folks mean by the term. "Hollywood" often seems to mean any movie in English, not the product of a certain system in a certain factory town. Also "Hollywood" is often pejorative, a shorthand for whatever criticism one cares to imply without examining it.